Executing Learning Activities and Autonomy-Supportive Instructions Enhance Autonomous Motivation - Hinnersmann, Paul; Hoier, Katrin; Dutke, Stephan (Frontiers in Psychology, 2020)
This study investigated situational changes in learners’ degree of autonomous regulation during other-initiated learning activities and examined the influence of the instructional style on such changes. To this end, relative autonomous motivation of 172 fifth to seventh grade students was measured before, during and after execution of a musical learning activity. It was experimentally manipulated whether students were instructed in an autonomy-supportive or a controlling style. As expected based on self-determination theory and the action-based model of cognitive dissonance, relative autonomous motivation increased in the course of the execution of the learning activity. Unexpectedly, this increase was only statistically significant when students were instructed in a controlling style. At all times though, students instructed in an autonomy-supportive style were more autonomously motivated than students instructed in a controlling style. Furthermore, results showed a positive effect of an autonomy-supportive instructional style on students’ functional state and their interest in continuing with the learning activity. The pattern of changes in relative autonomous motivation might indicate that in controlling conditions a reduction of dissonance is of functional importance, which is why relative autonomous motivation increased under controlling conditions but not under autonomy-supportive conditions. In an applied perspective, the study demonstrates that executing an activity might be beneficial for fostering autonomous motivation and it corroborates findings that indicate positive effects of an autonomy-supportive instructional style on students’ motivation and functional state.